PENGARUH LATIHAN IMAGERY INTERNAL DAN EKSTERNAL ERHADAP KETEPATAN PASSING LAMBUNG PEMAIN SEPAK BOLA DI SSB PUTRA BUANA - Zulkarnaen; Mujriah; Rindawan (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2024)
This study examined the effect of internal and external imagery training on the accuracy of lofted passes among football players at SSB Putra Buana. The study used a two-group pretest-posttest experimental design. From a population of 48 players, 20 players aged 13-14 years who met the attendance and training-history criteria were selected and assigned to two treatment groups. Passing accuracy was measured before and after a six-week intervention using a lofted-passing accuracy test. Data were analyzed descriptively and supported by assumption tests and t-tests. The assumption tests indicated acceptable normality and homogeneity, with all reported p-values above 0.05. Both groups improved after the intervention, but the external imagery group showed a larger increase from 62% to 80% (+18%; p = 0.01) than the internal imagery group, which improved from 60% to 70% (+10%; p = 0.05). These findings suggest that, in this sample, external imagery was more effective for improving lofted-passing accuracy. Structured imagery training can therefore be considered as a complementary method in youth football technical training.